Consolidated criteria for reporting qualitative research (COREQ): a 32-item checklist for interviews and focus groups - TONG, ALLISON; SAINSBURY, PETER; CRAIG, JONATHAN (International journal for quality in health care, 2007)
Background. Qualitative research explores complex phenomena encountered by clinicians, health care providers, policy makers and consumers. Although partial checklists are available, no consolidated reporting framework exists for any type of qualitative design. Objective. To develop a checklist for explicit and comprehensive reporting of qualitative studies (indepth interviews and focus groups). Methods. We performed a comprehensive search in Cochrane and Campbell Protocols, Medline, CINAHL, systematic reviews of qualitative studies, author or reviewer guidelines of major medical journals and reference lists of relevant publications for existing checklists used to assess qualitative studies. Seventy-six items from 22 checklists were compiled into a comprehensive list. All items were grouped into three domains: (i) research team and reflexivity, (ii) study design and (iii) data analysis and reporting. Duplicate items and those that were ambiguous, too broadly defined and impractical to assess were removed. Results. Items most frequently included in the checklists related to sampling method, setting for data collection, method of data collection, respondent validation of findings, method of recording data, description of the derivation of themes and inclusion of supporting quotations. We grouped all items into three domains: (i)research team and reflexivity, (ii) study design and (iii) data analysis and reporting. Conclusions. The criteria included in COREQ, a 32-items checklist, can help researchers to report important aspects of the research team, study methods, context of the study, findings, analysis and interpretations.